MODERNIZATION OF ISLAMIC CURRICULUM IN BALANCEING TRADITION AND INNOVATION FOR THE FUTURE OF COMING GENERATIONS - Hamsir, Hamsir; Zamroni, Zamroni; Tamam, Badrut (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Islamic education has undergone rapid transformation along with the development of the times. Modernization of the Islamic curriculum is needed to answer the increasingly complex challenges of the future, where tradition and innovation must go hand in hand. This article discusses the importance of modernizing the Islamic curriculum to accommodate future needs without abandoning traditional values that have proven their relevance and benefits. The main focus of this discussion is how the Islamic curriculum can integrate innovation without sacrificing the essence of existing Islamic teachings and the challenges faced in its implementation. This study uses a qualitative approach with literature studies as the main method to analyze the role of the Islamic curriculum in balancing tradition and innovation.